Implementing Digital Supply Chain Management to Improve Efficiency: A Case Study of Indocup Sablon - Damanik, Muhammad Rifki; Nurbaiti, Nurbaiti; Rahma, Tri Inda Fadhila (Majapahit Journal of Islamic Finance and Management, 2025)
Digital transformation in supply chain management has become a strategic necessity to improve company efficiency and competitiveness, especially in the small and medium enterprise (SME) sector. This study aims to analyze the implementation of Digital Supply Chain Management (DSCM) in improving company operational efficiency, with a case study of Indocup Sablon. The study used a qualitative descriptive approach through interviews, observation, and documentation techniques. The results show that the implementation of DSCM stages such as digital order receipt and processing, structured production planning, real-time inventory management, automated procurement systems, production recording, digital quality control, and customer management and feedback has resulted in significant efficiency improvements. Production time efficiency increased by 20%, order errors decreased by 35%, and logistics costs decreased by 15%. Despite facing challenges such as limited infrastructure and human resources, the implemented gradual digitalization strategy was able to have a significant positive impact on operational performance. These findings are expected to serve as a strategic reference for other SMEs wishing to implement a digital-based supply chain system.